Adolescent Identity Formation of Raib in the Novel Bumi by Tere Liye A Study of James Marcia’s Identity Status Theory - Faqih Dinar; Muhammad Hamdan Mukafi (Sabda: Jurnal Kajian Kebudayaan, 2026)
This article examines the identity formation of Raib, the main character in Bumi by Tere Liye, through James Marcia’s adolescent identity status theory. The study aims to describe the dynamics of Raib’s identity development through four statuses: identity diffusion, foreclosure, moratorium, and identity achievement, while also interpreting Tamus as a symbolic representation of adolescent ego. This study uses a qualitative descriptive method with a literary psychology approach. The data source is the novel Bumi (2014), while the data consist of narration and dialogues related to Raib’s psychological development. Data were collected through close reading, note-taking, and classification, then analyzed interpretatively based on Marcia’s framework. The findings show that Raib’s identity develops gradually: she initially accepts herself as an ordinary teenager (diffusion), then experiences external pressure from Tamus that shapes identity through coercive influence (foreclosure), continues with active self-exploration after gaining knowledge about her origins and powers (moratorium), and finally reaches stable self-acceptance and commitment as a member of Klan Bulan (identity achievement). In addition, Tamus functions symbolically as a figure representing adolescent ego and external pressure in the identity formation process.Keywordsadolescent identity; Raib; Bumi novel; James Marcia; literary psychology; Tere Liye